Falls after Hospital Discharge: A Randomized Clinical Trial of Individualized Multimodal Falls Prevention Education - Hill, Anne-Marie; McPhail, S.M.; Haines, T.P.; Morris, M.E.; Etherton-Beer, C.; Shorr, R.; Flicker, L.; Bulsara, M.; Waldron, N.; Lee, D.C.A.; Francis-Coad, J.; Boudville, A.; et al. (OXFORD UNIV PRESS INC, 2019)
Background: Older people are at high risk of falls after hospital discharge. The study aimed to evaluate the effect of providing individualized falls prevention education in addition to usual care on falls rates in older people after hospital discharge compared to providing a social intervention in addition to usual care.